Late Pleistocene-Holocene history of a tectonically active segment of the continental margin (Nekor basin, Western Mediterranean, Morocco). (November 2018) - Lafosse, M.; Gorini, C.; Le Roy, P.; Alonso, B.; d'Acremont, E.; Ercilla, G.; Rabineau, M.; Vázquez, J.T.; Rabaute, A.; Ammar, A.
Abstract: In active basins, tectonics can segment the continental shelf and control its stratigraphic architecture and physiography. Segmentation can explain the local evolution and morphology of the continental shelf because of sea-level variations, local tectonic segmentation and hydrodynamic processes. Here we investigate the tectonically active Morocco continental margin (southern Alboran Sea) using high-resolution seismic profiles and multibeam bathymetric data. The active faults bounding the transtensive Nekor basin triggered the segmentation of the shelf into three sectors showing different subsidence rates: a western sector corresponding to an extensive fault relay, a central sector corresponding to the subsiding Al-Hoceima Bay and an eastern sector corresponding to the footwall of the Trougout senestral normal fault. Results show that the staircase morphology of the shelf corresponds to successive submarine terraces at the shelf edge (ST1), mid-shelf (ST2) and inner-shelf (ST3) around −110 m, -80 m, and −40 to −20 m deep, respectively. The terraces correspond to the top of prograding wedges seaward and are erosive landward. They are correlated with stillstand from the Last Glacial Maximum to the Holocene highstand. Above the terraces, sub-aqueous dune fields are interpreted as degraded and deposited during the post-glacial transgression. In the central sector, typical delta front seafloor undulations on the shelf and crescent shaped bedforms at the head of marine incisions on the upper slope denote a fluvial influence during the Holocene. Seismic stratigraphy analysis revealed the preservation of six seismic units bounded by polygenic regional unconformities (S1, S2, S3, S4 and S5). Based on comparison with other Mediterranean margins, S1 to S5 are attributed to 4th order maximum regressive surface. We discuss the local preservation of the system tracts as a function of the vertical motion and the physiography of this tectonically active domain. This study provides useful clues for future local paleo-seismic analysis and to advance our understanding of sedimentary processes in active areas. Highlights: We present new data of the morphology of the Mediterranean Moroccan shelf. Marine terraces are present and correlated to local sea level variations. The active tectonic locally segments the shelf and control the stacking pattern. The relation between the stacking pattern and the morphology is investigated. We propose a depositional model correlating the morphology and the stratigraphy of the shelf.